Increased miR-6132 promotes deep vein thrombosis formation by downregulating FOXP3 expression - Zhang, Yunhong; Zhang, Zhen; Li, Haoyang; Chu, Chu; Liang, Gang; Fan, Nannan; Wei, Ran; Zhang, Tingting; Li, Lihua; Wang, Bin; Li, Xia (Frontiers in Cardiovascular Medicine, 2024)
Background Deep vein thrombosis (DVT) is associated with aberrant gene expression that is a common peripheral vascular disease. Here, we aimed to elucidate that the epigenetic modification of forkhead box protein 3 (FOXP3) at the post-transcriptional level, which might be the key trigger leading to the down-regulation of FOXP3 expression in DVT. Methods In order to explore the relationship between microRNAs (miRNAs) and FOXP3, mRNA and microRNA microarray analysis were performed. Dual luciferase reporter assay was used to verify the upstream miRNAs of FOXP3. Quantitative real-time polymerase chain reaction, flow cytometry and Western blot were used to detect the relative expression of miR-6132 and FOXP3. Additionally, DVT models were established to investigate the role of miR-6132 by Murine Doppler Ultrasound and Hematoxylin-Eosin staining. Results Microarray and flow cytometry results showed that the FOXP3 expression was decreased while miR-6132 level was increased substantially in DVT, and there was significant negative correlation between miR-6132 and FOXP3. Moreover, we discovered that overexpressed miR-6132 reduced FOXP3 expression and aggravated DVT formation, while miR-6132 knockdown increased FOXP3 expression and alleviated DVT formation. Dual luciferase reporter assay validated the direct binding of miR-6132 to FOXP3. Conclusion Collectively, our data elucidate a new avenue through which up-regulated miR-6132 contributes to the formation and progression of DVT by inhibiting FOXP3 expression.